PENANGGULANGAN KEKERASAN DI LINGKUNGAN SEKOLAH MELALUI IMPLEMENTASI PROGRAM SEKOLAH RAMAH ANAK - Miftahul Wahdah; Yuniar Mujiwati (IKIP PGRI Bojonegoro, 2020)
Abstract: This research aims to describe the prevention of violence in the environment of children through the Implementation of the Child-Friendly School Program in SMP Negeri 1 Pasuruan. The description is related to the Child-Friendly School Program as well as supporting and inhibiting factors in implementing the Child-Friendly School Program. This research uses descriptive qualitative research. The subjects of this research are the principal, teachers, students, and parents of students with the object of research including the implementation of the SRA Program at SMPN 1 Pasuruan. Data analysis techniques include data collection, data reduction, data presentation, and verification/conclusion drawing. The results of this research showed that the Child-Friendly School Program at SMPN 1 Pasuruan included (1) Communication, socialization of the Child Friendly School Program to all related parties such as teachers, students and parents; (2) human resources and infrastructure resources that support the Implementation of the Child-Friendly School Program and financial resources that draw on BOS funds; implementing the Child-Friendly School Program based on 3P namely Provision, Protection, Participation. Supporting factors are human resources, infrastructure resources, and financial resources. While the inhibiting factor is the lack of environmental hygiene conditions. Keyword: Violence, Program of Child-Friendly School Abstrak: Penelitian ini bertujuan untuk mendeskripsikan penanggulangan kekerasan di lingkungan anak melalui Implementasi Program Sekolah Ramah Anak di SMP Negeri 1 Kota Pasuruan. Deskripsi tersebut terkait dengan Program Sekolah Ramah Anak serta faktor pendukung maupun penghambat dalam mengimplementasikan Program Sekolah Ramah Anak. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Subjek penelitian ini yaitu kepala sekolah, guru, siswa, dan orang tua siswa dengan objek penelitian meliputi implementasi Program Sekolah Ramah Anak di SMPN 1 Pasuruan. Teknik analisis data meliputi pengumpulan data, reduksi data, penyajian data, dan verifikasi/penarikan kesimpulan. Hasil penelitian menunjukkan bahwa Program Sekolah Ramah Anak di SMPN 1 Pasuruan meliputi (1) Komunikasi, adanya sosialisasi mengenai Program Sekolah Ramah Anak kepada seluruh pihak terkait seperti guru, siswa dan orang tua; (2) Sumber daya manusia dan sumber daya sarana prasarana yang mendukung Implementasi Program Sekolah Ramah Anak dan sumber daya finansial yang mengambil dari dana BOS; menerapkan Program Sekolah Ramah Anak berdasarkan 3P yaitu Provisi, Proteksi, Partisipasi. Faktor pendukungnya adalah sumber daya manusia, sumber daya sarana prasana, dan sumber daya finansial. Sedangkan faktor penghambatnya adalah pada kondisi kebersihan lingkungan yang kurang. Kata kunci: Kekerasan, Program, Sekolah Ramah Anak.